Students’ Interest in the SQ3R Method for Completing Academic Tasks at the Indonesian Language Education Program, UIN Jakarta - Putrie Mauladanin Azama; Suhairiyah Suhairiyah; Widia Astuti; Hindun Hindun (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study investigates the interest of students in the Indonesian Language and Literature Education Program (PBSI) at UIN Jakarta regarding the SQ3R method (Survey, Question, Read, Recite, Review) for completing academic assignments. The research aims to assess students' interest in using SQ3R, their perceptions of its benefits for academic tasks, and their tendency to apply this method in academic reading. The research uses a descriptive survey design with a quantitative approach. A questionnaire was distributed to 42 students from the 2023 cohort, measuring three aspects of interest: (1) interest in SQ3R, (2) perceived benefits in academic tasks, and (3) tendency to apply the method. The results showed a high level of interest in the SQ3R method, with 97.6% of respondents expressing interest in understanding it more deeply and using it for academic tasks. Furthermore, students perceived SQ3R as an effective tool for improving reading and writing outcomes, with 95.2% agreeing that it helped them prepare academic papers. The study concludes that SQ3R is a well-received and beneficial method, though consistent application remains a challenge.